Outcomes of early post-discharge cardio-geriatric care in frail patients after acute heart failure: a before-and-after study - Chukwuma Okoye; Tessa Mazzarone; Alberto Finazzi; Guarino Daniela; Adriana Antonella Bruni; Lorenzo Maccioni; Giulia Pescatore; Maria Giovanna Bianco; Cinzia Guerrini; Andrea Giusti; Giuseppe Bellelli; Agostino Virdis (BMC Geriatrics)
Abstract Background Despite significant advancements in heart failure (HF) management, older adults continue to face poor clinical outcomes. While an integrated, multidisciplinary approach that combines cardiology and geriatric expertise has shown considerable promise, its adoption in practice remains limited. This study aimed to assess whether an early post-discharge Cardio-Geriatric (CG) outpatient service could reduce 1-year mortality compared to usual care (UC), as well as evaluate its impact on 1-year rehospitalization rates and days alive and out of hospital (DAOH). Methods In this single-center, controlled before-and-after study, patients aged ≥ 75 years hospitalized for acute HF were included. In the UC group, patients discharged between January 2018 and December 2019 received standard follow-up with referrals to a cardiologist and general practitioner. In the CG group, patients discharged between January 2020 and July 2022 attended CG ambulatory care within three weeks of discharge. Primary outcomes were one-year all-cause mortality, HF readmissions, and DOAH. The impact of CG follow-up was assessed using a 1:1 propensity score matched (PSM) analysis. Results A total of 652 patients (mean age 86 years, 56% female) were included in the study, with 477 receiving UC and 175 referred to CG follow-up. Following a 1:1 PSM of 350 patients (50% CG), we observed a significant reduction in 1-year rehospitalizations (36.5% vs. 50.8%, p < 0.001) and mortality (20.0% vs. 40.0%, p < 0.001) in the CG group. CG patients also had nearly double median DAOH compared to UC patients (300 [IQR: 100] vs. 162 [145] days, p < 0.001). Cox regression analysis confirmed that the CG integrated approach was independently associated with a lower risk of mortality [HR 0.34, 95% CI: 0.24–0.47]. Respiratory diseases, neurological conditions, and infections were common causes of readmission. Conclusions Early referral to a CG outpatients service post-discharge for acute HF significantly improves outcomes, highlighting the value of integrated care for older adults with complex needs.